Necesidad de reformar el libro segundo, titulo v, art.innumerado 43 del código de la niñez y adolescencia, en lo referente a la indexación automática anual dentro de las pensiones de alimentos - Bermeo Villarreal, Welington Xavier (2016)
The importance and significance of the problem socio-legal concerns "need to reform the Book II, Title V, ART.INNUMERADO 43 of the Code of Children and Adolescents, REGARDING THE ANNUAL AUTOMATIC INDEXING PENSIONS IN FOOD" and when analyzed carefully the interest arose to study this subject because every day we observe the violation of the rights of the obligor which is not benefited from a raise every year, but if it is increased by a percentage the monthly pension to the feed. The Constitution of the Republic of Ecuador guarantees the right to defense as well as protecting the interests of children and adolescents among others, the same as long ago as today have been made in breach annoying thing or complicated since automatic indexing of alimony was implanted in our Code of Children and Adolescents, thereby hurting many obligors, the same as if it is true to cover alimony fixed had many disadvantages which becomes even more difficult now that had to automatically increase these pensions, so many obligors have found it impossible to cancel these large sums of money; since in many cases by their meager income does not allow them to cover this amount, which causes the actors of the food trials proceed to request the ballot of urgency and defendants are deprived of their liberty harming minors and the bound leaving totally defenseless without recourse to any body that can give you some exit or help; Like similar case happens with the defendants who are public employees whose salary increases do not take place every year as in the case of the military and police on active duty. For this reason I have seen fit to do this work of socio legal research in which a detailed analysis is set to reform the automatic indexing in the Code for Children and Adolescents, as any measure of conceptual, legal and doctrinal views; This indexing is unconstitutional and harms both the obligor and the fed.